Results of Spanish accession to the European Communities upon regional labour markets - Piecuch, Jakub (Rezultaty przystąpienia Hiszpanii do Wspólnot Europejskich na regionalne rynki pracy, 2011)
One of the most significant indicators of social situation in the European Union member states and their regions is unemployment rate level and job-creation potential. The following article presents changes on the labour market of Spanish autonomous communities as a result of integration with the European Union structures. Economic and social differences among well-developed regions and the remaining autonomous communities have been significant, and during the last few years these differences have been increasing systematically. This situation causes concern, because the most important aim of the European Cohesion Policy is to narrow regional economic and social differences.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 180, s. 178-187
Keywords: labour market; economic development; region